PENGARUH BRAND AWARENESS DAN RELIGIUSITAS TERHADAP KEPUTUSAN PEMBELIAN CUSTOMER PRODUK PRO ISRAEL - Maulana, Adelia Putri Nazti; Safaatillah, Nurus; Uzlifatul, Lilik; Sustyorini, Emalia Nova (Universitas Nusa Cendana, 2024)
Garnier, a new product from PT. L'oreal Indonesia offers affordable prices and various variants with the latest innovations. However, political and religious controversies involving Israel often create negative perceptions of pro-Israel products. The focus of this research is the analysis of the influence of Brand Awareness and Religiosity on customer Purchasing Decisions of pro-Israel products on Garnier products at Abel Store. This study aims to determine the influence of Brand Awareness and Religiosity on Purchasing Decisions. This study used a sample of 105 respondents with the method of quantitative analysis and processed using Smart PLS. The results of this study show that Brand Awareness and Religiosity have a positive and significant effect, partially and simultaneously. Keywords: Brand Awareness; Religiosity; Purchasing Decisions